PI3K/Akt/mTOR: A promising therapeutic target for non-medullary thyroid carcinoma. Issue 8 (September 2015) - Petrulea, Mirela S.; Plantinga, Theo S.; Smit, Jan W.; Georgescu, Carmen E.; Netea-Maier, Romana T.
Abstract : Highlights: PI3K/Akt/mTOR pathway is a key player in pathogenesis of thyroid cancer (TC). Activation of PI3K/Akt/mTOR promotes tumor cell proliferation and dedifferentiation. Antitumorigenic mechanisms are inhibited, including apoptosis and autophagy. PI3K/Akt/mTOR inhibition is promising strategy for systemic therapy in advanced TC. PI3K/Akt/mTOR influences RAI uptake and is target for redifferentiation strategies. Abstract: Thyroid carcinoma (TC) is the most common endocrine malignancy. The pathogenesis of TC is complex and involves multiple genetic events that lead to activation of oncogenic pathways such as the MAP kinase (MAPK) pathway and the PI3K/Akt/mTOR pathway. The PI3K/Akt pathway has emerged as an important player in the pathogenesis of TC, particularly in follicular and advanced anaplastic or poorly differentiated TC. Because these patients have a poor prognosis, particularly when their tumors become resistant to the conventional treatment with radioactive iodine, efforts have been made to identify possible targets for therapy within these pathways. Orally available drugs targeting the PI3K/Akt/mTOR pathway are being used with success in treatment of several types of malignant tumors. There is an increasing amount of preclinical and clinical data supporting that this pathway may represent a promising target for systemic therapy in TC. The present review focuses on the most recent developments on the role of the PI3K/Akt pathway in the pathogenesis of non-medullary TC and will provide insight into how this pathway can be targeted either alone or in the context of multimodal therapeutic strategies for treatment of advanced TC.